Apparel-based industrializatrion in the Caribbean Basin : a threadbare garment? - Mortimore, Michael (1999)
Notes that the apparel-base industrialization in the Caribbean Basin can be said to be a 'threadbare garment' because - instead of deepening national industrialization it truncates it. The exports do not represent the external projection of the local industrialization process but merely the assembly of imported components. The local apparel companies are not internationalized in the process, but instead have their very existence threatened.